PERAN DARI LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN (LPSK) DALAM PEMERKOSAAN - Juwita Panjaitan, Clasina Mutiara; Putri, Ariyani (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2013)
AbstractIndonesia is a State based on law (rechstaat). The statement explicitly listed in the Constitution of the General Explanation of 1945. It is important to state law is the appreciation and commitment to uphold human rights and guarantees all citizens equal before the law (equality before the law).Practice of law enforcement is often tinged with things that are contrary to these principles. For example the persecution of suspects to pursue recognition, intimidation, engineering matters, extortion and so on. Then of the victims also feel their rights are ignored, such as the charges are weak, soft demand, not knowing the handling of the case, does not receive compensation and other rights. Demands need to be given to the protection of witnesses who have information about a crime to make the government along with the House of Representatives managed to devise a law that accommodates the protection of witnesses. Based on the principle of equality before the law which is one characteristic of the rule of law, a witness in the criminal justice process should be given legal protection. Until finally, on August 11, 2006 Law No. diundangkanlah.13 of 2006 on the Protection of Witnesses and Victims. Protection of witnesses in the criminal justice process in Indonesia has not been dealt with specifically. In Article 184 of the Criminal Code has been mentioned that the various items of evidence such as witness testimony, expert testimony, Letters, Instructions and Information defendant. Demands need to be given to the protection of witnesses who have information about a crime to especially make government corruption along with the House of Representatives managed to devise a law that accommodates the protection of witnesses. Based on the principle of equality before the law (equality before the law), which became one of the characteristics of law, a witness in the criminal justice process should be given legal protection. Until finally, on August 11, 2006 Law No. diundangkanlah.13 of 2006 on the Protection of Witnesses and Victims.Although Indonesia has Law No. 13 of 2006 on the Protection of Witnesses and Victims (Law on Witness and Victim Protection) which was enacted on August 11, 2006, but formally this Act is still judged to be maximal in the set of witnesses and victims perlindugan because there are shortcomings here and there. It is not surprising to see emergence of any way this law could stop the process of the discussion in the House about five years and seem only to meet the demands of society .Function of the Witness and Victim Protection Agency (Agency) in the case of human rights violations associated with Law No. 13 Year 2006 on the Protection of Witnesses and Victims. Problems studied are how forms of government protection afforded to victims of rape, other forms of protection provided, the filing mechanism, as well as the things that determine the existence of the Agency.Keywords: Roles, Witness and Victim Protection